DETERMINATION OF MEDICAL EDUCATION ENVIRONMENT IN PUNJAB PRIVATE AND PUBLIC MEDICAL COLLEGES AFFILIATED WITH UNIVERSITY OF HEALTH SCIENCES, LAHORE-PAKISTAN - Khan, Junaid Sarfraz; Tabasum, Saima; Yousafzai, Usman Khalil (Journal of Ayub Medical College Abbottabad, 2009)
Background: The main purpose of this study was to identify differences, if any, in the Medical Education Climate between the Private and Public Medical Colleges in the Province of Punjab affiliated with the University of Health Sciences, Lahore and to gather recommendations from students on measures that need to be taken to improve the environment. Methods: This Mixed Quantitative and Qualitative Prospective Study was conducted in 2008. The population of the study consisted of 1612 MBBS Final Year Medical Students of both Private and Public Medical Colleges. Stratified Random Sampling was done to ensure representation of both Sectors. Dundee Ready Education Environment Measure (DREEM) was used to assimilate Quantitative Data and a Questionnaire consisting of 10 items was used to accumulate Qualitative Data. To analyse Quantitative Data, t-test and Chisquare tests were used. Common themes were identified in the Qualitative Data. Results: All the SIX Research Hypotheses were rejected and Null Hypotheses were upheld. Analysis of Qualitative Data indicated a number of Examination, Curriculum, Teaching Methodology, Teacher and Peer related Stressors without discrimination in students of both Private and Public Sectors. Solutions by students focused on improving co-ordination between Institutions and University of Health Sciences as well as developing and delivering Clinically-Centred, Community-Oriented and Problem-Based Education through development of appropriate Teaching Methodologies. Conclusions: Even though there is no difference in the Medical Education Climate between the Private and Public Medical Education Sectors, the Environment is less than Ideal. However, this can be improved through shifting the onus of Education from Teacher-Centred Didactic Approach to a more Student-Centred SelfLearning Strategy. In this paradigm shift the UHS, Lahore needs to play a pivotal role in order to effectively train the Trainers and standardise this change throughout Punjab. Keywords: Medical Education Environment, Private Medical Sector, Public Medical Sector, DREEM, Problem-based Education, MCAT, COME, PBL